The Effect of Physical Exercise on Quality of Life in Chronic Kidney Disease Patients Undergoing Hemodialysis - Maldina, Saffira Hazya; Armelia, Linda; Poerwanto, Eko; Novita, Henny; Urfa, Meutia Lieska (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2024)
Background: Chronic kidney disease leads to a progressive and irreversible decline in kidney function, necessitating lifelong treatments such as dialysis or kidney transplantation. Patients undergoing hemodialysis (HD) often encounter challenges such as muscle weakness, which can frequently precipitate feelings of hopelessness and premature aging. These challenges can lead to medical, social, economic, and psychological issues that profoundly affect their quality of life. Objective: This study aimed to determine the effect of physical exercise on the quality of life of patients undergoing HD. Methods: This research was a correlational study using a cross-sectional approach. The population comprised chronic kidney disease patients undergoing HD at Anna Medika Hospital, Bekasi. There were 38 respondents who met the inclusion criteria. The analysis of the research data was conducted using the Wilcoxon test. Results: The study yielded quality of life results after physical exercise, with both the good and moderate categories showing the same result of 47.4%, while the bad category had 5.3%. Conclusion: There is a significant improvement in quality of life after physical training compared to before.